Antecedents of Employees Retention in Labor Market in Saudi Arabia - Nassani, Abdelmohsen A.; Alotaibi, Ftoun (The Arab Journal of Administration, 2024)
Employee retention is a crucial factor that drives the attention of organizations. The objective of this study is to explore the factors that affect employee retention in the labor market in Saudi Arabia. It focuses specifically on person-organization fit, work-life balance, and job satisfaction as antecedents that affect employee retention. The study used an online survey to collect responses to examine the antecedents. The questionnaire was statically analyzed using SPSS and Amos. The total number of respondents that participated in the study is 250 from both genders and variations in experience and age. The key findings of the study show that person-organization fit and Work-life balance have emerged as major antecedents which impact job satisfaction and retention. It discusses the effect of job satisfaction as a mediator between Person-Organization fit and retention. In addition, it discusses the effect of job satisfaction as a mediator between work-life balance and retention.